2017
DOI: 10.1186/s13024-017-0156-1
|View full text |Cite
|
Sign up to set email alerts
|

APOE Genotype Differentially Modulates Effects of Anti-Aβ, Passive Immunization in APP Transgenic Mice

Abstract: Background APOE genotype is the foremost genetic factor modulating β-amyloid (Aβ) deposition and risk of sporadic Alzheimer’s disease (AD). Here we investigated how APOE genotype influences response to anti-Aβ immunotherapy.MethodsAPPSW/PS1dE9 (APP) transgenic mice with targeted replacement of the murine Apoe gene for human APOE alleles received 10D5 anti-Aβ or TY11-15 isotype control antibodies between the ages of 12 and 15 months.ResultsAnti-Aβ immunization decreased both the load of fibrillar plaques and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Some AD immunotherapies have been found to be dependent on standard Fc receptor-based mechanisms (Bard et al, 2000;Koenigsknecht-Talboo et al, 2008;Liao et al, 2018), whereas other AD immunotherapies have shown ability to clear their protein targets independent of the Fc receptor (Bacskai et al, 2002;Das et al, 2003;Lee et al, 2016). Furthermore, both ApoE isoform and TREM2 function have been found to modulate the efficacy of anti-amyloid immunotherapy (Pankiewicz et al, 2017;Xiang et al, 2016). These results likely mean that a combination of both the correct protein target (or correct conformation of the protein), along with optimization of other properties of the antibody, are required both for the correct signaling pathways to be activated and the therapy to be truly effective.…”
Section: Discussionmentioning
confidence: 99%
“…Some AD immunotherapies have been found to be dependent on standard Fc receptor-based mechanisms (Bard et al, 2000;Koenigsknecht-Talboo et al, 2008;Liao et al, 2018), whereas other AD immunotherapies have shown ability to clear their protein targets independent of the Fc receptor (Bacskai et al, 2002;Das et al, 2003;Lee et al, 2016). Furthermore, both ApoE isoform and TREM2 function have been found to modulate the efficacy of anti-amyloid immunotherapy (Pankiewicz et al, 2017;Xiang et al, 2016). These results likely mean that a combination of both the correct protein target (or correct conformation of the protein), along with optimization of other properties of the antibody, are required both for the correct signaling pathways to be activated and the therapy to be truly effective.…”
Section: Discussionmentioning
confidence: 99%
“…APOE isoform-dependent effect on Aβ accumulation in APP/PS1/EKI mice While APOE may influence AD pathogenesis in several ways, one of the major mechanisms is via its effect on Aβ accumulation in the brain, specifically on Aβ seeding and clearance. As previous APOE knock-in mice have been shown to influence Aβ deposition in an isoformdependent fashion [5,6,8,9,43,56,57], we wanted to assess the effects of the major human APOE isoforms in the new APOE-KI model. Specifically, we investigated the effect of different human APOE alleles on Aβ accumulation in APP/PS1-21 transgenic mice.…”
Section: Qualitative Assessment Of Microglia and Astrocyte-derived Apmentioning
confidence: 99%
“…Since presence of the e4 allele is thought to reduce Aβ clearance, this underscores the importance of immune clearance of toxic proteins from the brain in preventing AD symptoms. In fact, APOE alleles have been found to impact the efficacy of passive anti-Aβ immunization suggesting that the different alleles effect microglia's phagocytic ability for Aβ (Pankiewicz et al, 2017). -Kopec et al, 2009) rs679515, rs3818361…”
Section: Ad Associated Genesmentioning
confidence: 99%